Previous Sternotomy as a Risk Factor in Minimally Invasive Mitral Valve Surgery - Minol, Jan-Philipp; Akhyari, Payam; Boeken, Udo; Albert, Alexander; Rellecke, Philipp; Dimitrova, Vanessa; Sixt, Stephan Urs; Kamiya, Hiroyuki; Lichtenberg, Artur (Frontiers in Surgery, 2018)
Abstract Background: Cardiac redo surgery, especially after a full sternotomy, is considered a high-risk procedure. Minimally invasive mitral valve surgery (MIMVS) is a potential therapeutic approach. However, current developments in interventional cardiology necessitate additional discussion regarding the therapy of choice in high-risk patients. In this context, it is necessary to clarify the peri- and postoperative risk induced by the factor previous sternotomy in the setting of MIMVS. Thus, we present a comparative study analysing the outcome of MIMVS after previous sternotomy versus primary operation. Methods: We identified 19 patients who received isolated or combined mitral valve (MV) surgery via the MIMVS approach after previous full sternotomy (PS group) and compared the results to those of a group of 357 patients who received primary MIMVS (non-PS group). After a propensity score analysis, groups of n = 15 and n = 131, respectively, were subjected to a comparative evaluation. A 1-year follow-up analysis of functional cardiac parameters and clinical symptoms was performed, accompanied by a Kaplan-Meier analysis. Results: Except for the rate of realized MV reconstructions (PS group: 53.8% vs. non-PS group: 85.5%; p = 0.011), no significant differences were to be noted within the intraoperative and early postoperative course. However, patients in the PS group experienced an increased ICU stay length (PS group: 2 days, 95% CI 1-8 vs. non-PS group: 1 day, 95% CI 1-2; p = 0.072). The follow-up examinations revealed excellent functional and clinical outcomes for both groups. The Kaplan-Meier analysis displayed no significant difference regarding the postoperative mortality (p = 0.929) related to the patients at risk. Conclusions: A previous sternotomy remains a risk factor for MIMVS, and demands special attention in the early postoperative period. Nevertheless, the early and late-term results concerning the functional and clinical outcomes suggest that the MIMVS procedure is satisfactory, even after a full-sternotomy.